Inhibition of IL-1β by Aliskiren Improved Renal AQP2 Expression and Urinary Concentration Defect in Ureteral Obstruction and Release - Hu, Shan; Xie, Haixia; Luo, Renfei; Feng, Pinning; Liu, Qiaojuan; Han, Mengke; Kong, Yonglun; Zou, Xuenong; Wang, Weidong; Li, Chunling (Frontiers in Physiology, 2019)
We previously demonstrated that ureteral obstruction is associated with a urinary concentrating defect and reduced expression of renal aquaporins (AQPs), in which the renin–angiotensin system (RAS) may play an important role. The aims of the present study were to examine whether the renin inhibitor aliskiren could prevent the reduction in AQP expression and improve the urinary concentrating capacity in mice with bilateral ureteral obstruction (BUO) and BUO release. BUO was performed for 24 h, and BUO release was performed for 1 (B-R1D) or 3 days (B-R3D) with or without aliskiren treatment. Aliskiren prevented polyuria and decreased urine osmolality induced by B-R3D. In mice with BUO and BUO release, aliskiren attenuated the reduction in AQP2 protein and mRNA expression in the obstructed kidneys. B-R3D increased the protein expression of NLRP3 inflammasome components ASC, caspase-1, and interleukin-1β in the obstructed kidneys, which was markedly prevented by aliskiren. Moreover, the NF-κB inhibitor Bay 11-7082 blocked NLRP3 inflammasome activation and attenuated the decrease in AQP2 protein expression in primary cultured rat inner medullary collecting duct cells treated with angiotensin II. These results indicate that the renin inhibitor aliskiren increases water channel AQP2 expression at least partially by suppressing NLRP3 inflammasome activation in the obstructed kidneys of mice with BUO and BUO release.